Judy [videorecording (DVD)] - Goold, Rupert; Zellweger, Renée, 1969-; Buckley, Jessie, 1989-; Wittrock, Finn, 1984-; Quilter, Peter (Lionsgate, 2019)
A biography of the late singer/actress Judy Garland.